2019
DOI: 10.3389/fmats.2019.00127
|View full text |Cite
|
Sign up to set email alerts
|

Synergetic of Pt Nanoparticles and H-ZSM-5 Zeolites for Efficient CO2 Activation: Role of Interfacial Sites in High Activity

Abstract: Catalytic systems prepared by controlled processes play an important role in the utilization of CO 2 via catalytic hydrogenation to produce useful C1 chemicals (such as CO, CH 4 , and CH 3 OH), which will be vital for forthcoming applications in energy conversion and storage. Size-controlled Pt nanoparticles were prepared by a polyol method and deposited on H-ZSM-5 (SiO 2 /Al 2 O 3 = 30, 80, and 280) zeolite supports. The prepared catalysts were tested for the CO 2 hydrogenation in the temperature range of T =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(8 citation statements)
references
References 49 publications
0
8
0
Order By: Relevance
“…7.9°and 8.9°, corresponding to the [011] and [200] planes of a typical MFItype zeolite, 63 which is in line with the reported XRD pattern for H-ZSM-5 with a SiO 2 /Al 2 O 3 molar ratio of 23 18,47 and within the range 30−280. 64 Diffraction peaks from the Al 2 O 3 matrix are hardly present in the H-ZSM-5/Al 2 O 3 catalyst (Figure 6a), implying that the crystallinity of the γ-Al 2 O 3 binder is by far lower than that of the ZSM-5 zeolite. 65 27 Al MAS ssNMR spectrum of Fresh catalyst (Figure 7A-a) displays three peaks from Al atoms in different coordination environments.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…7.9°and 8.9°, corresponding to the [011] and [200] planes of a typical MFItype zeolite, 63 which is in line with the reported XRD pattern for H-ZSM-5 with a SiO 2 /Al 2 O 3 molar ratio of 23 18,47 and within the range 30−280. 64 Diffraction peaks from the Al 2 O 3 matrix are hardly present in the H-ZSM-5/Al 2 O 3 catalyst (Figure 6a), implying that the crystallinity of the γ-Al 2 O 3 binder is by far lower than that of the ZSM-5 zeolite. 65 27 Al MAS ssNMR spectrum of Fresh catalyst (Figure 7A-a) displays three peaks from Al atoms in different coordination environments.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Lowfrequency CO vibration (under 1790 cm −1 ) has been observed in CO adsorption on Mn, La, Ce, Fe promoted Rh/SiO2 catalysts [111][112][113]. The same feature appeared on Pt/zeolites during CO2 hydrogenation [114]. It was suggested that Lewis acid sites caused the downward shift of the CO ligand vibration through the interaction between the Lewis acid and the oxygen atom of CO.…”
Section: Co 2 Hydrogenation On Titania and Titanate Supported Rhmentioning
confidence: 81%
“…The parent HZSM-5 catalyst had a typical NH 3 -TPD profile, with two maximal peaks at low and high temperatures. The desorption of NH 3 from Lewis sites (weak acid sites) (such as extra-framework aluminum) has been attributed to the low-temperature desorption peak at 216 °C [ 67 , 68 ], while the desorption of NH 3 from the Bronsted acid sites (strong acid sites) deriving from framework aluminum has been attributed to the high-temperature desorption peak at 439 °C [ 69 , 70 , 71 ]. Figure 5 shows that the peak areas indicated the number of acid sites and that the peak temperatures were assigned the acid strength [ 34 ].…”
Section: Resultsmentioning
confidence: 99%